Racial And Gendered In/Visibility: Reading Jhumpa Lahiri's Fiction As A Response To The Objectification Of The Diasporic Subject In The West - Asl, Moussa Pourya (2018)
The Indian diaspora writer Jhumpa Lahiri’s fiction has been the subject of abundant yet controversial criticism. Whereas some acknowledge her truthful representations of diaspora experience, others have charged her with a limited vision that encourages, legitimizes and transmits only one favored reality. This research aims to investigate whether her fiction adheres to or deviates from prevailing racial and gendered hierarchies of the mainstream. To fulfill this underlying aim, the study offers a new interpretive model that seeks to evince the political, cultural and affective consequences of Lahiri’s diasporic writings and their particular enunciations of the literary gaze.